Climate Change and Agriculture 2019
DOI: 10.5772/intechopen.87982
|View full text |Cite
|
Sign up to set email alerts
|

Salinity Stress in Arid and Semi-Arid Climates: Effects and Management in Field Crops

Abstract: Salinity stress is one of the most vital abiotic stresses which results in significant damages of agricultural production, particularly in arid and semi-arid areas of the world. Salinity causes by high accumulation of soluble salt, especially NaCl in soil and water. Salinity hampers the growth and survival of many field crops such as rice, wheat, maize, cotton, sugarcane, and sorghum. It affects the plant growth by three ways such as osmotic stress linked with an increase of phytotoxic ions, ionic stress e in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
74
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(100 citation statements)
references
References 90 publications
1
74
0
Order By: Relevance
“…Salt stress causes severe oxidative stress to plants in addition to causing the osmotic stress linked with an increase in phytotoxic ions in the cytosol [74]. High salinity induces the formation of ROS, which can accumulate to cause membrane deterioration, lipid peroxidation, and DNA modification.…”
Section: Overexpression Of Osexpa7 Improved Oxidative Stress Tolerancementioning
confidence: 99%
“…Salt stress causes severe oxidative stress to plants in addition to causing the osmotic stress linked with an increase in phytotoxic ions in the cytosol [74]. High salinity induces the formation of ROS, which can accumulate to cause membrane deterioration, lipid peroxidation, and DNA modification.…”
Section: Overexpression Of Osexpa7 Improved Oxidative Stress Tolerancementioning
confidence: 99%
“…These hubs could play a principal role in the arid zones associated with spineless cacti. Indeed, several studies reported that these strains were often associated with deserts and biocrust habitats and their adaptation to extreme environmental conditions, such as high salt concentration, low relative humidity, and high UV radiation, has been described (Hussain et al, 2019;Pombubpa et al, 2019). Moreover, bacterial species related to these genera have been defined as endophytes associated with arid plants and some of them possess the ability to protect the host plants and promote their growth (Trujillo et al, 2015;Singh and Dubey, 2018).…”
Section: Factors Affecting the Assembly Of Microbial Communities In Smentioning
confidence: 99%
“…These zones are characterized by high temperatures and low precipitations, and they are probably the most threatened by desertification. Abiotic stress, including high and low temperature, water deficit (drought) and flooding, salinity, UV radiation, light, and poor nutrient soils, have a significant impact on soil fertility and subsequently on agricultural production in semi-arid and arid regions (Shahid and Al-Shankiti, 2013;Cuevas et al, 2019;Hussain et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Salinity stress is one of the major challenges threatening food security and restricting crop productivity [1][2][3][4]. This abiotic stress affects the agricultural sector on a global scale.…”
Section: Introductionmentioning
confidence: 99%